2015
DOI: 10.1097/fpc.0000000000000138
|View full text |Cite
|
Sign up to set email alerts
|

Genetic ancestry as an effect modifier of naltrexone in smoking cessation among African Americans

Abstract: Objectives To determine if there were differential quit rates between AA and European Americans (EA) with the experimental treatment naltrexone, and examine the role of genetic ancestry on these outcomes among AAs. Methods Data from a previous randomized trial of 315 smokers to naltrexone vs. placebo were reanalyzed using West African (WA) genetic ancestry to define sub-populations. Logistic regression models were used to estimate treatment effects on early and end of treatment quit rates, by race and WA anc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 62 publications
0
15
1
Order By: Relevance
“…The fact that 94% of study participants were African American is different from most previous alcohol trials. Previous data suggest that naltrexone may not be as effective in African Americans than other racial groups (Bress et al., ; Ray and Oslin, ), and this could have contributed to the relative lack of an effect in our study.…”
Section: Discussioncontrasting
confidence: 52%
“…The fact that 94% of study participants were African American is different from most previous alcohol trials. Previous data suggest that naltrexone may not be as effective in African Americans than other racial groups (Bress et al., ; Ray and Oslin, ), and this could have contributed to the relative lack of an effect in our study.…”
Section: Discussioncontrasting
confidence: 52%
“…Although the social and cultural influences of race on disease are undeniable, the role of genetics cannot be ignored. For example, an admixed individual with 20% EUR genetic ancestry may be at greater or lesser risk of certain diseases than an individual with 40% EUR genetic ancestry (56)(57)(58)(59)(60). In addition, the implications for pharmacogenomics exist as the nuances of drug effects or mechanisms may not be generalizable in the African American population due to high WA genetic variance (28,61).…”
Section: Discussionmentioning
confidence: 99%
“…Analyses were repeated using percentage of West African ancestry as a continuous variable normalized by the SD of the distribution, and by partitioning participants in 2 groups defined by the median split of the ancestry distribution. 29 For all analyses, missing covariate data were imputed with 10 data sets using chained equations. 37 The number and percentage of participants with missing data for each variable included in this analysis are reported in Supplementary Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…24 The AIMS from the Nigerian parental population (i.e., HAPMAP YRI) are very useful proxies for West African Ancestry as these markers vary widely across continental populations but not within West and Central Africans. [25][26][27][28][29][30][31] A recent analysis of the genetic makeup of African Americans using more than 450,000 single-nucleotide polymorphisms found that African Americans are genetically derived mostly from West and West-Central African ancestral populations. 32 Moreover, an analysis of the 1000 Genomes Project sequence data found that the smallest genetic distance (Fixation index or F ST ) for African Americans is with the Yoruba from Nigeria.…”
Section: West African Ancestrymentioning
confidence: 99%